XORIJIY TILLARGA O’RGATISH MUAMMOLARI VA ZAMONAVIY YECHIMLARI - Nigina, Hamidova (FILOLOGIYA UFQLARI JURNALI, 2021)
Today, the communicative approach is recognized as a priority in foreign language teaching methods around the world. In many European countries, the communicative approach, which leads to effective results in teaching a foreign language, differs from traditional teaching in that it focuses on teaching communication, the main function of language - teaching to communicate. The main purpose of this is to teach students to communicate in a foreign language using a complex of linguistic, psychological, didactic, methodological factors, tools and methods promoted by various disciplines, which help to effectively organize the learning activities of students.